Stray dogs as carriers of E. coli resistant strains for the retracted and re-emerged antibiotic colistin, based on the mcr-1 gene presence - Ioannis Tsakmakidis; Anastasia Parisi; Dimitrios K. Papadopoulos; Maria V. Alvanou; Konstantinos V. Papageorgiou; Evanthia Petridou; Ioannis A. Giantsis (AIMS Molecular Science)
Antimicrobial resistance (AMR) is becoming a major problem for animal and human health. Reports of resistance to colistin, an antibiotic that is considered a last resort drug against resistant Gram-negative bacteria, have been increasing over the last years. Among the different mechanisms that cause AMR to colistin, the mobilized colistin resistance (mcr) gene has been reported as responsible for the increased incidence in animals and humans since 2015. There are ten recognized distinct variants of this gene in bacteria isolated from animals, humans, food, and the environment. Companion animals could have a role in human infection by pathogenic and resistant E. coli strains as they share the same environment and are in close contact with humans. Considering this, our aim was to investigate antimicrobial resistance in companion domestic and stray dogs in Western Macedonia, Greece. Our results revealed that of the 43 individual fecal samples examined, 16% of them hosted the mcr-1 gene, all of which were isolated from stray dogs. Our results suggested that companion dogs and stray dogs can serve as reservoirs for colistin-resistant E. coli strains.